Idealism, Realism and Hints of Personalism in C.I. Lewis. - HERRMAN, CHARLES S. (Studia Philosophica Wratislaviensia, 2023)
This paper examines the arguments of C.I. Lewis respecting the utility of idealist and realist philosophical categories and ends with a look at his personalist credentials. It is reported that Lewis pared away the outer layer of idealism leaving its utility in explaining perception via his concept of the “given”. This resulted in a fundamentally realist vision with the exception of perceptive theory. It is off ered that the realist perspective is the more satisfactory metaphysical component of a healthy personalist philosophy, one that Lewis would presumably favor.